Identification of factors and outcomes of trust in mobile supply chains - Nassim Ghondaghsaz; Sven Engesser (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - The main purpose of this paper is the identification of the conceptualization of trust as well as its factors and outcomes in interorganizational relations in mobile supply chains (MSCs) in which multiple stakeholders collaborate. Design/methodology/approach - The authors first used a comprehensive literature review to extract related factors and outcomes of trust. Second, the authors conducted semi-structured interviews in chemical and pharmaceutical companies in Germany. These organizations stand out as leaders in the concept of MSCs and have developed collaborations with various stakeholders. Findings - Based on the results, a conceptual model has been developed that elaborates on the nature of trust and its factors and outcomes for cultivating trustful stakeholder collaboration. The study identifies six factors or approaches for building trust and two outcomes resulting from mutual trust. Practical implications - The conceptual model presented in this study can serve as a basis for developing trust in MSCs. Interorganizational collaborations in MSCs are more successful when saturated with trust. The collaboration systems must allow the innovative organizations to create value through the adaptation of advanced technologies without failure. Originality/value - The study adds to the body of knowledge in building trust in multiple stakeholder collaboration, particularly in innovative organizations which are involved with disruptive technologies.
Keywords: 650; Information sharing; Interorganizational trust; Mobile supply chain; Stakeholders; Supply chain collaboration; Sustainable production